Effects of terminal biphenyl ring geometry on the photophysical properties of closo-o-carboranyl–anthracene dyads. Issue 31 (30th June 2021) - Hong, Ju Hyun; Im, Sehee; Seo, Yung Ju; Kim, Na Young; Ryu, Chan Hee; Kim, Mingi; Lee, Kang Mun
Abstract : Four anthracene-based closo-o -carboranyl compounds bearing phenyl or biphenyl substituents at C10 were prepared to establish a design strategy for enhancing the solution- and solid-state emissive properties. Abstract : Four anthracene-based compounds bearing phenyl (AC ) or biphenyl ( o AC, m AC, and p AC ) substituents at C10 and a closo-o -carboranyl unit at C9 were prepared and fully characterized to establish a design strategy for enhancing the solution- and solid-state emissive properties of closo-o -carboranyl luminophores at ambient temperature. In all solid-state molecular structures, the anthracene moieties were severely distorted because of intramolecular steric hindrance, which indicated that structural variation around the o -carborane cage was strongly inhibited. Compared to the other o -carboranyl compounds, o AC, possessing an ortho -type biphenyl group, exhibited much higher emission intensity, quantum efficiency, and radiative decay constant in tetrahydrofuran solution and film state at 298 K. The electronic transitions calculated for first excited states showed that emission originated from intramolecular charge-transfer (ICT) transitions involving o -carborane. The ground-state energy barriers were calculated based on the relative energies at dihedral angles centered at the bonding axis between anthracene and (bi)phenyl groups and implied that the rotational motion of the terminal (bi)phenyl rings was less restricted in o AC than in the other compounds. Furthermore, the orbital contributions calculated for electronic transitions in the first excited state indicated that structural variation around the terminal (bi)phenyl rings suppressed ICT transitions. The above findings reveal that the molecular rigidity of the moiety appended to aromatic rings in o -carboranyl–anthracene dyads strongly affects the efficiency of their ICT-based emission and suggest that this emission can be enhanced via the attachment of rigid substituents to o -carboranyl luminophores.